Qualitative Study of Barriers to Adherence to Antihypertensive Medication among Rural Women in India. (23rd January 2019) - Gupta, Shreya; Dhamija, Jas Pal; Mohan, Indu; Gupta, Rajeev
Abstract : Objective . There is poor adherence to antihypertensive therapies among women in India. To determine its socioeconomic barriers we performed a qualitative study on Indian rural women with hypertension. Methods . In-depth interviews with women having hypertension and presenting to outpatient department at a teaching hospital were performed in 30 women aged 35-65 years, using a questionnaire focused on reasons for nonadherence and poor lifestyle modification. Low to medium adherence was observed in two-thirds of women. Results . Majority of women were from low socioeconomic status and were illiterate. Awareness of hypertension and its complications was poor. Knowledge and practices of cessation of smoking and tobacco use and salt restriction in hypertension were low. Efforts to increase physical activity and decrease dietary fat and sugar intake were largely absent. Local follow-up at rural community health centres was not practiced due to physician nonavailability and about half used alternative systems of medicine. None had health insurance or access to free medicines. All the women had to pay out-of-pocket for medicines and were concerned with cost of therapy as well as pill burden. Half of the women borrowed money from relatives or friends to reach the hospital and pay for medicines. Conclusions . Socioeconomic barriers for low adherence to antihypertensive medication in women in India are low awareness of hypertension and complications, poor access to care, out-of-pocket payments, borrowing money, lack of insurance, and cost of medicines.